2004
DOI: 10.1074/jbc.m310616200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ser-386 of Interferon Regulatory Factor 3 as Critical Target for Inducible Phosphorylation That Determines Activation

Abstract: Interferon regulatory factor (IRF)-3 is a critical transcription factor regulating innate immune responses against viral and bacterial infections. Signals activated by various pathogens are integrated by IRF-3 kinase, resulting in the specific phosphorylation of IRF-3 in the cytoplasm. This phosphorylation induces dimerization and association with the coactivators CREB-binding protein/p300, and the resultant complex activates the target genes in the nucleus. However, the phosphorylation sites that determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(196 citation statements)
references
References 26 publications
(49 reference statements)
8
185
1
Order By: Relevance
“…However, a more recent report has questioned the importance of Ser396 as the primary phosphoacceptor site and instead provides data to indicate that Ser386 is the crucial residue that undergoes inducible phosphorylation, thus leading to IRF3 activation [45]. This study provides a more satisfying mechanistic basis for TRIF activation of IRF3 because both TBK1 and IKK-I can phosphorylate IRF3 at Ser386 and the engagement of TLR3 and TLR4 by dsRNA and LPS leads to phosphorylation of this residue.…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 85%
See 1 more Smart Citation
“…However, a more recent report has questioned the importance of Ser396 as the primary phosphoacceptor site and instead provides data to indicate that Ser386 is the crucial residue that undergoes inducible phosphorylation, thus leading to IRF3 activation [45]. This study provides a more satisfying mechanistic basis for TRIF activation of IRF3 because both TBK1 and IKK-I can phosphorylate IRF3 at Ser386 and the engagement of TLR3 and TLR4 by dsRNA and LPS leads to phosphorylation of this residue.…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 85%
“…However, the phosphorylation has a key role in promoting the transactivation of IRF3 by facilitating its association with the co-activator CBP. In light of the study by Mori et al [45], it would be interesting to determine if Ser386 is the residue phosphorylated by Akt.…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 99%
“…In some experiments, HCV proteins were detected with hyperimmune patient serum [obtained from W. Lee (University of Texas Southwestern Medical Center, Dallas) with informed consent]. Specific methods for analysis of IRF-3 dimerization using nondenaturing gel electrophoresis were followed as described elsewhere (15). Immunostaining procedures used the indicated primary antibodies in combination with Alexa Fluor 488 or Rhodamine-conjugated specific secondary antibodies (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…IFN regulatory factor 3 (IRF-3) 3 is a ubiquitously expressed transcription factor that regulates primary induction of type I IFN, IFN-␣␤, and plays a critical role for establishing innate immune status in response to invasion of pathogens (1-2, 4). Although IRF-3 is retained in the cytoplasm of unstimulated cells, it is phosphorylated and forms a dimer upon viral infection, which then translocates to the nucleus, binds to IFN stimulation response element (ISRE) and enhances the transcription of a set of genes including IFN-␤ (2,4,5). Recent studies revealed that two noncanonical I B kinase (IKK)-like kinases, NF-B-activating kinase (NAK)/Traf family member-associated NF-B activator-binding kinase 1 (TBK1) and IKK-i/IKK⑀, could induce the dimerization of IRF-3 by enhancing phosphorylation of IRF-3 and play essential roles for IRF-3-dependent transcriptional activation (6,7).…”
Section: A20 Is a Negative Regulator Of Ifn Regulatorymentioning
confidence: 99%
“…pcDNA3 and pISRE-luc were purchased from Invitrogen Life Technologies and Stratagene, respectively. pcDNA3-FLAG-NAK, pcDNA3-FLAG-dnNAK (K38A), pEF-FLAG-IKK-i, pEF-HA-IRF-3, pEF-HA-dnIRF-3 (58 -427), and pEF-p50-IRF-3 5D were described previously (5,12,19,20). Complementary DNAs encoding either the N-terminal 378 aa (1-378) or Cterminal 412 aa (379 -790) of human A20 were amplified by PCR using pcDNA3-HA-A20 as a template and inserted into pcDNA3-HA.…”
Section: Plasmidsmentioning
confidence: 99%